The effect of process-oriented writing instruction on writer’s block, writing apprehension, attitudes towards writing instruction and writing performance - Akpınar, Fatma Betül (My University, 2007)
The effect of process-oriented writing instruction on writer’s block, writing apprehension, attitudes towards writing instruction and writing performance The present study aimed to investigate the effect of process-oriented writing instruction on writer’s block, writing apprehension, students’ attitudes towards writing instruction and writing performance. The study also attempted to investigate the relationship between writer’s block, writing apprehension, attitudes towards writing instruction and writing performance. The subjects of the study comprised 48 EFL university students in İstanbul. The experimental group received process-oriented writing instruction, while the control group received product-oriented writing instruction. Data were collected by means of the Writing Apprehension Scale developed by Daly and Miller (1975), the Writer’s Block Questionnaire developed by Rose (1984), the Literacy Scale developed by Lee (2002), the essay tasks given before and after the treatment and the interviews. Findings revealed that the students who had process-oriented writing instruction experienced less writing apprehension than the participants who had product-oriented writing instruction. As for the changes from pre-treatment to post-treatment, both groups demonstrated statistically significant improvement in writer’s block and writing performance. Moreover, the findings obtained in this study indicated that the relationship between writing apprehension and writer’s block was positive and meaningful. However, the relationship between the students’ attitudes towards writing instruction and other variables was not significant. Furthermore, the study yielded a negative relationship between writer’s block and writing performance of the students who received process-oriented writing instruction.
Keywords: Yabancı Dil_Gramer; Yabancı Dil_İngilizce; Yazma_İngilizce